Analisis Kesalahan Pengucapan dalam Membaca Huruf Hijaiyah: Kajian Fonologi - Syifa Salsabila Fitrianingrum; Elfiana Fitri Aminingsih (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This research discusses pronunciation errors of Arabic letters (Hijaiyah) in children aged 9-10 years, examined within the field of phonology. The study is motivated by the observation that children exhibit deficiencies in the pronunciation of Arabic letters due to their non-participation in Taman Pendidikan Al-Qur'an (TPQ) activities and other factors influencing the mispronunciation of Arabic letters. In the preparation of this article, the researcher employed a qualitative descriptive methodology with a case study focusing on phonological errors in the pronunciation of Arabic letters by elementary school children aged 9-10 years. The aim of this research is to analyze pronunciation errors in reading Arabic letters (Hijaiyah) among children aged 9-10 years. From the research findings, it is evident that the subjects still make numerous errors in the pronunciation of Arabic letters. The conclusion drawn from this research is that a profound understanding of pronunciation errors in reading Arabic letters (Hijaiyah) among children aged 9-10 years allows for the development of more effective learning strategies, particularly in the context of phonological studies.